Effect of Solvent Type and Extraction Temperature of Chicken Leg on The Physical and Chemical Characteristic Producted Gelatine - Hadijah Siregar; Sentosa Ginting; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The aim of this research was to find the effect of solvent type and extraction temperature of chicken leg on the physical and chemical characteristic producted gelatine. The research was using completely randomized design with two factors, i.e solvent type (P): (acetic acid, chloride acid, and sulfuric acid) and extraction temperature (S) : (50 OC, 60 OC, 70 OC, and 80 OC). Parameters analyzed were yield, moisture content, ash content, protein content, pH, color and flavor.The results showed that solvent type had highly significant effect on yield, moisture content, ash content, protein content, pH, and color. The extraction temperature had highly significant effect on moisture content, ash content, color, and flavor. Interaction of the two factors had significant effect on moisture content, ash content and color. The sulfuric acid solution and extraction temperature 60 OC produced the best chicken leg gelatine. Keywords : Chicken leg, extraction temperature, gelatine, solvent type.